Evidence supporting endodontic therapy as a safe strategy in patients previously treated with head and neck radiotherapy: a scoping review - Álvaro Souza Wanderley; Wesley Viana de Sousa; Maria Olívia da Costa; Alícia Marcelly Souza de Mendonça Silva; Raylane Farias de Albuquerque; Igor Henrique Morais Silva; Lucas Nascimento Ribeiro; Diana Santana Albuquerque; Marlos Barbosa-Ribeiro (Supportive Care in Cancer, 2026)
Abstract Purpose To map and synthesize the available scientific evidence supporting the effectiveness and safety of endodontic therapy in patients who underwent head and neck radiotherapy, considering clinical and radiographic outcomes and treatment-related complications, particularly osteoradionecrosis (ORN). Methods This scoping review followed the Arksey and O’Malley framework, informed by the Joanna Briggs Institute Manual for Evidence Synthesis, and was reported according to PRISMA-ScR guidelines. Comprehensive searches were conducted in PubMed, Embase, Scopus, Web of Science, MEDLINE, LILACS, and gray literature sources, with no date restrictions. Clinical studies evaluating endodontic therapy in irradiated patients were included. Data were charted and narratively synthesized using a Population–Concept–Context framework. Consistent with scoping review methodology, no critical appraisal was performed. Results Of 174 identified records, five studies met the inclusion criteria. Reported success rates ranged from 18 to 100%, with lower rates observed in earlier studies employing outdated techniques. More recent investigations demonstrated high clinical success, improved radiographic stability, and no reported cases of ORN. Across all studies, endodontic therapy was not associated with ORN. However, methodological heterogeneity was noted, particularly regarding outcome definitions and follow-up duration. Conclusion Endodontic therapy appears to be a safe and conservative treatment option for patients with head and neck cancer who underwent radiotherapy and may reduce the need for invasive procedures associated with ORN risk. However, the limited and heterogeneous evidence highlights the need for well-designed prospective studies to support standardized clinical decision-making within supportive oncology care.